Diagnostic Values For Club Cell Secretory Protein (CC16) in Serum of Patients of Combined Pulmonary Fibrosis and Emphysema. (4th July 2015) - Kokuho, Nariaki; Ishii, Takeo; Kamio, Koichiro; Hayashi, Hiroki; Kurahara, Misuzu; Hattori, Kumiko; Motegi, Takashi; Azuma, Arata; Gemma, Akihiko; Kida, Kozui
Abstract Combined pulmonary fibrosis and emphysema (CPFE) is an under-recognized syndrome for which the diagnostic use of serum biomarkers is an attractive possibility. We hypothesized that CC16 and/or TGF-β1 or combinations with other biomarkers are useful for diagnosing CPFE. Patients with respiratory symptoms and a smoking history, with or without chronic obstructive pulmonary disease, were divided into the following three groups according to findings of high-resolution computed tomography of the chest: controls without either emphysema or fibrosis, patients with emphysema alone, and patients compatible with the diagnosis of CPFE. Serum concentrations of CC16, TGF-β1, SP-D, and KL-6 were measured in patients whose condition was stable for at least 3 months. To investigate changes in biomarkers of lung fibrosis in patients with a life-long smoking history, additional measurements were performed on the patients with idiopathic pulmonary fibrosis (IPF) of smoking history. The mean age of the first three groups was 68.0 years, whereas that of the IPF group was 71.8 years, and the groups contained 36, 115, 27, and 10 individuals, respectively. The serum concentration of CC16 in the four groups was 5.67 ± 0.42, 5.66 ± 0.35, 9.38 ± 1.04 and 22.15 ± 4.64 ng/ml, respectively, indicating that those patients with lung fibrosis had a significantly higher concentration. The combined use of CC16, SP-D, and KL-6 provided supportive diagnosis in conjunction with radiological imaging in diagnosis of CPFE. We conclude that a combination of biomarkers including CC16 could provide useful information to screen and predict the possible diagnosis of CPFE.